2007
DOI: 10.1029/2006jd007771
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical properties of the aerosol within the southeastern Pacific marine boundary layer

Abstract: Cloud condensation nuclei (CCN) concentrations at the peak in-cloud supersaturation and over a range in supersaturation were calculated using the collected data. The data were also used to quantify the number to volume concentration ratio of the accumulation mode aerosol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 54 publications
9
58
0
Order By: Relevance
“…by Bigg et al (1984); O'Dowd et al (1997), which is confirmed also by modelling studies (Adams et al, 1999). Particles of similar hygroscopicity and volatility as here were also recently measured in south-eastern Pacific by Tomlinson et al (2007). They measured hygroscopicities of particles to be on the order of, or even higher, than those of ammonium bisulphate.…”
Section: Particle Volatilitysupporting
confidence: 71%
See 1 more Smart Citation
“…by Bigg et al (1984); O'Dowd et al (1997), which is confirmed also by modelling studies (Adams et al, 1999). Particles of similar hygroscopicity and volatility as here were also recently measured in south-eastern Pacific by Tomlinson et al (2007). They measured hygroscopicities of particles to be on the order of, or even higher, than those of ammonium bisulphate.…”
Section: Particle Volatilitysupporting
confidence: 71%
“…Massling et al, 2007;Tomlinson et al, 2007). Swietlicki et al (2008) summarise various HGF measurements around the world and discuss the composition of the marine "more hygroscopic" particles.…”
Section: Hygroscopic Growth Factorsmentioning
confidence: 99%
“…Past shipboard measurements (Kollias et al, 2004;Petters et al, 2006;Tomlinson et al, 2007;Wood et al, 2008) reported an increase in the number of Aitken-mode aerosols in the very clean regions of the POCs, suggesting that the low aerosol concentrations in the POC allow for the nucleation of Aitkenmode aerosols. Their growth to accumulation-mode sizes Atmos.…”
Section: Aitken-mode Aerosolmentioning
confidence: 99%
“…Over the open oceans, there have only been a few recorded observations of new particle formation (Covert et al 1992(Covert et al , 1996aClarke et al 1998;Hoppel et al 1994;Ehn et al 2010). Observations of a significant nucleation event by Kollias et al (2004) in the southeastern Pacific appear to be due to emissions from South America (Tomlinson et al 2007). Examination of some of the experimental data indicates that under typical marine conditions, nucleation does not occur.…”
Section: Secondary Organic Marine Aerosolmentioning
confidence: 99%